2019
DOI: 10.1186/s13756-019-0636-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of antibiotics in six ethnic groups: the HELIUS study

Abstract: BackgroundThe increase of antimicrobial resistance, mainly due to increased antibiotic use, is worrying. Preliminary evidence suggests that antibiotic use differs across ethnic groups in the Netherlands, with higher use in people of non-Dutch origin. We aimed to determine whether appropriate knowledge and use of antibiotics differ by ethnicity and whether knowledge on antibiotics is associated with antibiotic use.MethodsWe performed a cross-sectional study analyzing baseline data (2011–2015) from a population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Despite the fact that we did not find any relationship between the BMI and antibiotic consumption, people who are overweight or obese are more likely to acquire an infection and thus need antibiotics compared with normal weight adults [59,60]. As found in another study [61], the likelihood of antibiotic consumption was greater in older people having a worse self-perceived health status, which may be because in a health system like the Spanish one, where access to care is universal, people with worse perceived health status visit their doctor regardless of their age. In the present study, the probability of antibiotic consumption was more than double in older people who had no polypharmacy.…”
Section: Discussioncontrasting
confidence: 62%
“…Despite the fact that we did not find any relationship between the BMI and antibiotic consumption, people who are overweight or obese are more likely to acquire an infection and thus need antibiotics compared with normal weight adults [59,60]. As found in another study [61], the likelihood of antibiotic consumption was greater in older people having a worse self-perceived health status, which may be because in a health system like the Spanish one, where access to care is universal, people with worse perceived health status visit their doctor regardless of their age. In the present study, the probability of antibiotic consumption was more than double in older people who had no polypharmacy.…”
Section: Discussioncontrasting
confidence: 62%
“…Both of these recent studies, as well as our own qualitative study, underline the worldwide trend towards lower expectations to receive antibiotics [ 32 ] and a decreasing trend in total antibiotic use in the European Union overall between 2011–2019 [ 23 ]. Moreover, they are consistent with the study of Schuts et al (2019) [ 18 ], which demonstrated no differences between six Dutch ethnic groups in the number of antibiotics used. Besides adapting to antibiotic guidelines in their host country, the reluctant antibiotic attitude of immigrants can also be derived from the implementation of antibiotic stewardship programs such as the National Action Plan (NAP), which was introduced in Turkey in 2014 [ 21 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…This might explain why we found considerable similarities between immigrant and native Dutch participants regarding antibiotic attitude and use. In the literature, discussions often focus on differences between first- or second-generation immigrants [ 13 , 18 ], but it can be expected that there are also differences between first-generation immigrants depending on their length of stay in the host country. Nevertheless, similar findings were also reported by other recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For COVID-19, our results suggested that inequalities in hospitalization risk were also attributable to the higher rate of comorbidities (i.e., diabetes and hypertension) in specific ethnic minority groups. We also found that levels of knowledge regarding antibiotics use and prescriptions varied between ethnic groups (36). This is of concern, as antimicrobial resistance can impact the treatment and prevention of bacterial infections.…”
Section: Infectious Diseasesmentioning
confidence: 76%